The assessment of Indonesian EFL students' reading comprehension ability using Reading Evaluation and Decoding System (READS) - Indah Fajar Wahyuni (UAD TEFL International Conference)
This study focused on reading comprehension ability of the English Department students in answering READS, MCQ questions. READS is an alternative standardized assessment system that is capable of measuring reading comprehension ability. This is a descriptive study based on Barrett's Taxonomy levels, such as literal comprehension, reorganization, and inferential comprehension. This study consisted of 122 students of the English Department academic year 2015 through 2018 at one of the private universities in Yogyakarta, Indonesia. This study analysis utilized the three Barrett's taxonomy scales to identify whether the students were at meet the standard, below standard, above standard or at academic warning. Finding of the research indicated that 27.8 % students categorized into academic warning (Band 2 and 3), 46.7% students categorized into below standard (Band 4) and 25.5% students categorized into meet standard (Band 5). Consequently, READS as an alternative assessment will guide the teachers to design specific reading material based on students' needs.